Targeting local orogenic gold mineralisation zones using data-driven evidential belief functions: the Godarsorkh area, Central Iran - Mehdi Maleki; Shojaeddin Niroomand; Shahrokh Rajabpour; Amin Beiranvand Pour; Salahadin Ebrahimpour (All Earth, 2022)
Using GIS-based multi-criteria decision-making techniques, i.e. mineral prospectivity mapping (MPM), specific spatial problems can be solved by combining information from different sources. Orogenic gold mineralisation shows weak exploration signals on the surface that can challenge exploration geologists. This study investigates the ability of a MPM method called evidential belief functions (EBFs) to identify a local orogenic gold mineralisation in the Godaesorkh gold deposit, north of Sanandaj-Sirjan Zone (Central Iran). Several evidential layers such as geological, structural, geophysical, remote sensing, and geochemical layers were generated by applying various processing methods. These layers are integrated to attain a MPM by applying the EBFs based on Dempster-Shafer’s rules. Precise selection of evidential layers and higher number of known mineral occurrences may lead to a higher degree of belief in the mineral prospectivity map. Accordingly, high probability values were correlated with the gold mineralisation in the study area, and three separate areas were identified as promising with N40E and N15W trends. It is concluded that the orogenic gold mineralisation occurred in shear zones, which is mainly controlled by tectonic structures. Consequently, analysing these structures can be considered as a key feature for identifying potential orogenic gold mineralisation zones in the study area.